Analysis of chosen polymorphisms in FoxP3 gene in children and adolescents with autoimmune thyroid diseases. (September 2014) - Bossowski, Artur; Borysewicz-Sańczyk, Hanna; Wawrusiewicz-Kurylonek, Natalia; Zasim, Aneta; Szalecki, Mieczysław; Wikiera, Beata; Barg, Ewa; Myśliwiec, Małgorzata; Kucharska, Anna; Bossowska, Anna; Gościk, Joanna; Ziora, Katarzyna; et al.
Abstract Introduction: Forkhead box P3 (Foxp3) is an important regulatory factor for the development and function of T regulatory (Treg) cells. Moreover, it has been established that deficiency of the Foxp3 gene in Treg cells suppresses their regulatory function leading to the development of autoimmune diseases especially autoimmune thyroid diseases. The aim of our study was to estimate the association of three polymorphism of FOXP3 gene with the predisposition to Graves' disease (GD) and Hashimoto's thyroiditis (HT) in children and adolescents. Materials and methods: The study was performed in the group consisting of 145 patients with GD (mean age, 16.5 ± 2 years), 87 patients with HT (mean age, 15.2 ± 2.2 years) sequentially recruited from the endocrinology outpatient clinic and 161 healthy volunteers (mean age, 16.3 ± 3 years). DNA was extracted from the peripheral blood leukocytes using a classical salting-out method. The three single nucleotide polymorphisms (SNPs) rs3761549 (−2383C/T), rs3761548 (−3279G/T) and rs3761547 (−3499T/C) in the FOXP3 gene were genotyped by TaqMan SNP genotyping assay using the real-time PCR method. The levels of thyroid hormones, TSH and anti-thyroid autoantibody were determined using chemiluminescence method. Results: In our study, rs3761549G/A genotype was more frequent in female patients with GD in comparison to healthy female (15% vs. 7%, p = 0.033) with OR = 2.15 and 95% confidence interval for OR: 1.07–4.63. We have also observed rs3761547T/C to be more frequent in females with GD in comparison to control females, and this difference was close to statistically important (13% vs. 7%, p = 0.066) with OR = 1.99 and 95% confidence interval for OR: 0.96–4.48. There were no significant differences in males in analyzed SNPs and in females with rs3761548 SNP. Conclusion: In conclusion, these results may suggest that rs3761549G/A polymorphism in Foxp3 gene could contribute to GD development in females.